The level of educational values that are practiced by the secondary school students in Bani Obaid Brigade based on their point of view - AL- ISSA, Asem ABDALLA SALAMEH (Journal of Educational and Psychological Sciences, 2019)
This study aims to identify the level of educational values that are practiced by the secondary school students’ in Bani Obaid Brigade in Irbid city based on their point of view. This study seeks to identify the differences in the responses of the sample members on their practices of educational values ​​according to two variables which are gender and streams. The study covered the total number of all students in the 11th grade of secondary school in Bani Obaid Brigade which is (1884) in the second semester of the academic year 2018/2019. Then, A random sample was chosen from the study population which consist of (754) equal to (4%) percent. After the researcher completed the investigation, the number of respondents who answered the questionnaire was (700). In order to achieve the objectives of the study, the researcher prepared a questionnaire which was finalized after the procedures of validity and reliability for (36) paragraphs. The paragraphs were divided into four scopes: worship scope, moral scope, the national scope, and the aesthetic scope. The results of the study are summarized in the following points: 1- Practicing of the secondary school students in the Bani Obaid Brigade for educational values ​represents the highest average which is (3.89) 2- There are statistically significant differences for the educational value ​​ attributed to the gender variable. The responses of the sample members showed the differences for the male students at level (α = 0.05) 3- There are not statistically significant differences at level (α = 0.05) in the responses of the sample members on the fields of educational values ​​due to the streams variable. 4- Based on the results of this study, the researcher recommends the teachers at the secondary schools at Bani Obaid Brigade in Irbid city to help the students to be more conscious about the necessity of the educational values which play a major role in their personal and social life. Similarly, the national value is one of most important values that the schools have to take care about it by encouraging the student to participate in the national events and festivals. Moreover, the researcher recommends the teachers to encourage the students to buy the national products in order to support the national economic. 5- The researcher suggests holding training courses for the teachers at Bani Obaid Brigade in Irbid city to improve their ability for learning students about the national values. Additionally, he recommends them to conduct researches that help to follow up the students’ behaviors for the educational values in the secondary schools.